Association of low back and knee pain with falls in Japanese community‐dwelling older adults: A 3‐year prospective cohort study. Issue 6 (20th May 2016) - Kitayuguchi, Jun; Kamada, Masamitsu; Inoue, Shigeru; Kamioka, Hiroharu; Abe, Takafumi; Okada, Shimpei; Mutoh, Yoshiteru
Abstract: Aim: To examine whether the chronicity and intensity of low back pain (LBP) or knee pain (KP) was associated with the occurrence of falls among a community‐dwelling older population. Methods: This was a community‐based 3‐year prospective cohort study. In 2009, baseline questionnaires were mailed to 3080 randomly selected residents aged 60–79 years; 2534 residents (82.3%) responded to the baseline survey, and 1‐ and 3‐year follow‐up surveys were subsequently mailed to them. The data for 1890 respondents who had no falls in the past year at baseline were analyzed. Associations between pain status (chronicity, intensity and persistence) and the occurrence of falls were analyzed by multivariable‐adjusted logistic regression. Results: A total of 197 (13.6%) participants had at least one fall during 12 months at 3‐year follow up; of those, 68 (4.8%) had multiple falls, and 65 (4.5%) resulted in an injury. Chronicity and intensity of LBP were associated with injurious falls ( P for trend = 0.033 and P for linearity = 0.041, respectively), and KP was associated with at least one fall ( P for trend = 0.021 and P for linearity = 0.040, respectively). In addition, participants who had chronic pain persistently at both baseline and 1‐year follow up had a higher risk of falls (LBP for injurious falls; adjusted odd ratio 2.46, 95% confidence interval 1.08–5.63, KP for at least one fall; adjusted odd ratio 2.39, 95% confidence interval 1.29–4.44), compared with those who had no pain at both time‐points. Conclusions: LBP and KP chronicity, intensity and persistence of chronic pain were associated with a greater risk of falls in older adults.Geriatr Gerontol Int 2017; 17: 875–884.